BIOLOGICAL CHARACTERISTICS AND IMPORTANCE OF THE SOYBEAN (GLYCINE MAX) - Pirnazarov Yerbol Bakir o‘g‘li; Tatayeva Dinara Abdulla qizi; Ahmadjonova Sevinchbonu Ulug‘bek qizi (Western European Studies, 2025)
The article examines the biological characteristics, significance, cultivation, and breeding of soybean (Glycine max). Soybeans, due to their high protein and oil content, are widely used in the food industry, medicine, agriculture, and industrial production. Particular attention is paid to its role in enriching soil with nitrogen and promoting sustainable agriculture. The botanical characteristics of the plant, including its structure, biological features, and adaptability, are discussed. Key aspects of soybean cultivation, such as climate requirements, soil conditions, agronomic practices, and yield, are analyzed. The focus is also on breeding efforts aimed at enhancing stress resistance, improving seed quality, and increasing productivity. In Uzbekistan, soybeans play an important role in the agricultural sector, serving as a source of vegetable oils and feeds, as well as contributing to soil fertility improvement through crop rotation. The significance of implementing modern technologies and breeding advancements to boost yields and enhance the country’s export potential is emphasized
Keywords: soybean; biological characteristics; cultivation